ANALYSIS OF THE IMPORTANT ROLE OF CHILDHOOD EDUCATION THROUGH ONLINE LEARNING SYSTEMS IN THE TIME OF COVID-19 - Khairun Nisa Bunaiya; Febriansyah Febriansyah (Proceeding International Seminar of Islamic Studies, 2022)
Education has a very important role and becomes capital in facing the future, where the role of education personnel is to support the progress and success of children in education. Therefore, to get a sample of the number of education personnel and the number of students who take online learning. This study uses a purposive sampling method by counting the number of education staff and students in order to balance the quality of students' comprehension. This study aims to find out how much the quality of education personnel and the quality of children's education in the online learning system during the Covid-19 period is where this analysis is carried out by observation, seeing firsthand the conditions and situations of the school environment. And facilities for education staff in carrying out online learning. This data analysis is divided into two parts, firstly how the teacher explains the title of the lesson to be studied and secondly how the students respond, where the results of the study show that the role of education personnel gives very good value. Provide online learning materials so that students can understand what has been conveyed by the teacher. However, for the sake of increasing the application of online learning, education staff from SMAN 1 Binjai also provide relief for students who do not have communication tools or telephones to study online, and make some changes for students who do not have communication tools. In order to be able to go to school and learn face to face, but by complying with health protocols, wearing masks and changing the distance between classrooms.Keywords: Analysis of Education Personnel, Quality of Children's Education, Online Learning System